2021
DOI: 10.2196/20319
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Technology and Social Media Use in Sleep-Onset Difficulties Among Italian Adolescents: Cross-sectional Study

Abstract: Background The use of technology and social media among adolescents is an increasingly prevalent phenomenon. However, there is a paucity of evidence on the relationship between frequency of use of electronic devices and social media and sleep-onset difficulties among the Italian population. Objective The aim of this study is to investigate the association between the use of technology and social media, including Facebook and YouTube, and sleep-onset dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 68 publications
5
21
0
1
Order By: Relevance
“…Similarly, as for the relation between PIU and EDS, we found additional evidence concerning the negative impact of maladaptive patterns of Internet use on sleep which was already described in literature 70 , 71 In particular it has been previously reported that PIU is related to many sleep problems, including reduction in sleep duration, 44–46 sleep onset difficulties, 42 , 47 insomnia and EDS. 72 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, as for the relation between PIU and EDS, we found additional evidence concerning the negative impact of maladaptive patterns of Internet use on sleep which was already described in literature 70 , 71 In particular it has been previously reported that PIU is related to many sleep problems, including reduction in sleep duration, 44–46 sleep onset difficulties, 42 , 47 insomnia and EDS. 72 …”
Section: Discussionsupporting
confidence: 83%
“…Generally, PIU is thought to lead to sleep deprivation. Indeed, it has been suggested that Internet use may cause a reduction in sleep duration 44–46 and sleep onset difficulties, 42 , 47 resulting in increased fatigue and sleepiness during the day.…”
Section: Introductionmentioning
confidence: 99%
“…Extended use of digital media screen time correlates with sleep impairment [ 18 , 21 , 22 , 26 , 31 , 43 , 47 , 49 , 57 , 61 , 63 , 64 , 65 ]. Table 6 summarizes the evidence in literature ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Portable electronic devices have further complicated this issue by providing adolescents with continuous, round-the-clock access to engaging and stimulating activities. Indeed, electronic device use among adolescents is associated in both cross-sectional and longitudinal studies with a range of sleep outcomes, including later, shorter, and poorer sleep [ 14 - 17 ], as well as daytime sleepiness [ 18 - 22 ]. Portable devices now offer teens access to communicate directly and indirectly with peers at any time of the day or night via social media.…”
Section: Introductionmentioning
confidence: 99%